2018
DOI: 10.5539/ijel.v9n1p178
|View full text |Cite
|
Sign up to set email alerts
|

Iraqi EFL Students’ Difficulties in Writing Composition: An Experimental Study (University of Baghdad)

Abstract: Iraqi EFL students face difficulties in writing composition, especially academic writing, which affects negatively their exam results. This study has been conducted in the Department of English at College of Education for Women, University of Baghdad, in order to identify first year EFL students’ incompetence in writing. This may enhance their achievement by some weekly writing activities. It deals with Iraqi EFL students’ difficulties in writing paragraphs such as descriptive, process, opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…As a result, a good cohesive and coherence on their essay writing are not existed since they perceived the cohesive and coherence problems (Ahmed, 2010;Belkhir & Benyelles, 2017;and Ariyanti & Fitriana, 2017). Further, the grammatical problems were also experienced by the EFL students in essay writing (Ariyanti & Fitriana, 2017;Hasan & Marzuki, 2017;and Nasser, 2019) covering plural forms, articles, verbs forms, clauses, passive voice and preposition. Furthermore, the mechanics problems of punctuation, spelling, handwriting also faced by the EFL students in their essay writing (Ariyanti &Fitriana, 2017 andNasser, 2019).…”
Section: E Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a good cohesive and coherence on their essay writing are not existed since they perceived the cohesive and coherence problems (Ahmed, 2010;Belkhir & Benyelles, 2017;and Ariyanti & Fitriana, 2017). Further, the grammatical problems were also experienced by the EFL students in essay writing (Ariyanti & Fitriana, 2017;Hasan & Marzuki, 2017;and Nasser, 2019) covering plural forms, articles, verbs forms, clauses, passive voice and preposition. Furthermore, the mechanics problems of punctuation, spelling, handwriting also faced by the EFL students in their essay writing (Ariyanti &Fitriana, 2017 andNasser, 2019).…”
Section: E Discussionmentioning
confidence: 99%
“…Their study found that the students met difficulties in both coherence and cohesion due to the lack of reading, first language transfer and low writing practice. Nasser (2019) diagnosed the Iraqi EFL students' writing composition difficulties and revealed that the students' errors were concerned on using grammar, punctuation, spelling, and handwriting.…”
Section: A Introductionmentioning
confidence: 99%
“…This idea is in line with Cahyono et al (2016), Husin and Nurbayani (2017), Jacobs (2013), Nasser (2018), andWeideman (2013). Many studies in academic writing at higher education contexts show that writing instruction must consider, among other things, the learning needs of students across disciplines and associated discourse genres (Bailey, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…However, there are considerable professionalism issues in assigning teachers particularly to teach research and technical report writing courses. That is, writing courses (Basic Writing Skills, Research, and Technical Report Writing) were being exclusively taught by host department teachers who are assumed to have subject matter (content) expertise regardless of their lack of qualification and expertise in ELT, if not also in the language itself (Fareed et al, 2016;Hyland & Hamp-Lyons, 2002;Kruse, 2007;Leung, 2008;Nasser, 2018;Wahyuni & Umam, 2017). English for academic purposes refers to language research and instruction that focuses on the specific needs and practices of particular groups in academic contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation